Adaptive preamble‐sampling techniques for receiver‐based medium access control protocols in lossy wireless sensor networks. (1st February 2015) - Akhavan, Mohammad Reza; Choobkar, Sabrieh; Aijaz, Adnan; Aghvami, Abdol‐Hamid
Abstract : In preamble‐sampling medium access control (PS‐MAC) protocols, nodes spend most of their time in sleep mode, and wake up for a short duration every checking interval (CI) to check the channel for an ongoing transmission. To avoid deafness, each data packet is preceded by a preamble with the same length as CI, to make sure that all potential receivers detect the preamble. In this work, the authors extend the idea of receiver‐based medium access control (MAC) protocol in which all potential neighbour nodes obtain the data frame. They propose and evaluate adaptive preamble MAC and adaptive sampling MAC in PS‐MAC with multiple receiver nodes. The analytical and numerical results demonstrate how proposed adaptive PS‐MAC outperforms the state‐of‐the‐art sender‐based and receiver‐based PS‐MAC protocols in terms of energy, while maintaining the comparable reliability in data delivery. In addition, overall lifetime of the involved sensor nodes has increased significantly.